1997
DOI: 10.1143/jjap.36.l435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2 Annealing on a Pt/PbZrxTi1-xO3 Interface Studied by X-Ray Photoelectron Spectroscopy

Abstract: In the first part of this article, we find fractional D3-branes supergravity solutions on orientifolded C 2 /Z 2 orbifolds of type-IIB string theory. The one-loop corrected gauge couplings for the symplectic or orthogonal groups living on the D-branes are reproduced on the world-volume of probes. In the second part of the paper, we construct a D3-brane solution on the two-centers Taub-NUT manifold which interpolates between fractional D3-branes in the ALE space limit and a T-dual smeared type-IIA configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 7 publications
4
19
0
Order By: Relevance
“…It has particularly been observed that the changes may already occur at room temperature. The strong dependence of the barrier height on the chemical state of the interface has also been reported by other groups [22,23]. The effect is not restricted to PZT/Pt but also observed at other oxide/metal interfaces [24,25].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…It has particularly been observed that the changes may already occur at room temperature. The strong dependence of the barrier height on the chemical state of the interface has also been reported by other groups [22,23]. The effect is not restricted to PZT/Pt but also observed at other oxide/metal interfaces [24,25].…”
Section: Introductionsupporting
confidence: 80%
“…While Pb can dissolve in Pt and therefore remain close to the interface, it is not dissolved in Cu and Ag and hence segregates to the surfaces of these films. The variation of barrier height observed with Pt contacts is accompanied by an increase/decrease of the metallic Pb species [16,22,23]. This suggests that the insensitivity of the barrier height on the metal work function is related [14], respectively, into account, the dipole potential δ can be derived form the discontinuity of the vacuum level E VAC at the interfaces.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[1][2][3][4][5] In our previous letter, we first revealed SBT degradation under reducing conditions by using bulk ceramic samples. 6 SBT decomposes into Bi metal and Sr-Ta-oxide phase͑s͒ through oxygen dissociation.…”
mentioning
confidence: 99%
“…Pb and/or oxygen defects in PZT were possibly introduced under the reducing conditions. 4,5 Since the reduced black sample almost recovered its whiteness through the subsequent annealing in oxygen, the oxygen defects are the main mechanism that best explains the change in the sample appearance after the annealing in H 2 and O 2 atmospheres.…”
mentioning
confidence: 99%